2018
DOI: 10.1016/j.virol.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious viruses persistently infect three commonly used mosquito cell lines

Abstract: Mosquito cell lines have been used extensively in research to isolate and propagate arthropod-borne viruses and understand virus-vector interactions. Despite their utility as an in vitro tool, these cell lines are poorly defined and may harbor insect-specific viruses. Accordingly, we screened four commonly-used mosquito cell lines, C6/36 and U4.4 cells from Aedes albopictus, Aag2 cells from Aedes aegypti, and Hsu cells from Culex quinquefasciatus, for the presence of adventitious (i.e. exogenous) viruses. All … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Importantly, Rps7 was amplified when genomic DNA was treated with RNase, but not DNase, confirming the purity of the DNA samples (Fig 2A). Although we cannot exclude the possibility that the primers we designed missed smaller fragments of integrated PCLV sequence, our data suggest that PCLV fragments are not integrated into the genome of parental Aag2 cells, which is in agreement with data from other research groups [56].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, Rps7 was amplified when genomic DNA was treated with RNase, but not DNase, confirming the purity of the DNA samples (Fig 2A). Although we cannot exclude the possibility that the primers we designed missed smaller fragments of integrated PCLV sequence, our data suggest that PCLV fragments are not integrated into the genome of parental Aag2 cells, which is in agreement with data from other research groups [56].…”
Section: Resultssupporting
confidence: 90%
“…Cell fusing agent virus (CFAV; family Flaviviridae , genus Flavivirus ) was the first insect-specific virus discovered and has long been known to persistently infect Aag2 cells and other Ae. aegypti cell lines [3,55,56]. In addition, we previously discovered Aag2 cells to be persistently infected with the insect-specific virus Phasi Charoen-like virus (PCLV; order Bunyavirales , family Phenuiviridae , genus Phasivirus ) [57].…”
Section: Introductionmentioning
confidence: 99%
“…Schultz et al screened their mosquito cell lines and discovered a persistent infection of CFAV and PCLV [ 104 ]. Further, Weger-Lucarelli et al screened the four widely used mosquito cell lines C6/36, U4.4, Aag2 and HSU and confirmed that all four cell lines were persistently infected with several viruses [ 109 ]. This should to be considered when designing an experiment or analysing data generated from these cell lines.…”
Section: Vector Competence Studiesmentioning
confidence: 99%
“…Of note, different strains of a particular cell line do not necessarily contain the same persistent infections. For example, Weger-Lucarelli et al identified only CYV in U4.4 cells [218], while our U4.4 cells are additionally infected with the ISVs PCLV and CFAV. Cross-contamination between insect cell lines is a risk, as in most laboratories cell lines are passaged in parallel.…”
Section: Discussionmentioning
confidence: 53%
“…With the introduction of next-generation sequencing (NGS) technologies and metagenomics into the field of virology, it becomes increasingly clear that many insect cell lines and insects, including mosquitoes, carry persistently infecting ISVs [217][218][219][220]. To investigate the presence of ISVs in our Cx.t and U4.4 cells, the libraries of small RNA reads of these two cell lines were subjected to de novo assembly.…”
Section: Discovery Of Insect-specific Viruses By De Novo Assembly Of mentioning
confidence: 99%